Design of a Virtual Reality Interactive Training System for Public Health Emergency Preparedness for Major Emerging Infectious Diseases: Theory and Framework - Yue Luo; Mei Li; Jian Tang; JianLan Ren; Yu Zheng; XingLi Yu; LinRui Jiang; DingLin Fan; YanHua Chen (JMIR Publications, 2021)
BackgroundSufficient public health emergency preparedness (PHEP) is the key factor in effectively responding to and recovering from major emerging infectious diseases (MEIDs). However, in the face of MEIDs, PHEP is insufficient, so it is necessary to improve PHEP. The rapid development of virtual reality and human-computer interaction provides unprecedented opportunities for innovative educational methods. ObjectiveThis study designed a virtual reality interactive training system (VRITS) to provide an effective path for improving PHEP in the context of MEIDs so that the public can effectively respond to and recover from MEIDs. MethodsThis study used interactive narrative, situated learning and human-computer interaction theories as a theoretical framework to guide the design of the system. We used the literature research method and the Delphi method; consulted multidisciplinary experts, such as infectious diseases, disease control, psychology, and public health personnel, to determine the educational content framework; and set up an interdisciplinary team to construct an operating system framework for the VRITS. ResultsWe named the VRITS "People's War Against Pandemic." The educational content framework includes 20 knowledge, emotion, and behavior skills in 5 aspects (cooperating with prevention and control work, improving emergency response ability, guaranteeing supplies and equipment, preparing economic resources, and maintaining physical and mental health). The operating system framework includes virtual interactive training, knowledge corner, intelligent evaluation, and community forum modules, and the core module is the virtual interactive training module. In this module, users control virtual characters to move in various scenes, and then identify and analyze the controllability and harmfulness of the evolving pandemic and select the correct prevention and control strategy to avoid infecting themselves and others. ConclusionsThe development and sharing of the multidisciplinary theoretical framework adopted by People's War Against Pandemic can help us clarify the design ideas and assumptions of the VRITS; predict training results; understand the ability of training to change emergency knowledge, emergency emotion, and behavioral responses to MEIDs; and promote the development of more effective training systems based on virtual reality.